Scolariser les enfants en tentant de contrôler les parents. Le cas des enfants du voyage en France - Virginie Dufournet Coestier; Gilles Monceau (Sociétés et Jeunesses en Difficulté)
Non-sedentary parents have particular relationships with school, how does the school interact with them? Does it seek to influence their educational practices, in what way and with what effects? In France, education is compulsory but not schooling. This rule applies to all students but in a differentiated way. The school attendance of those whom the Ministry of National Education has designated as “Children from Traveling Families and Travelers (EFIV)” by a 2012 circular, has for decades been subject to a specific control that must be relocated in a story to be understood. Research has therefore mobilized a socio-historical approach to better understand the uncertainties of this schooling policy and the categorizations it has successively created. The results of an ethnographic survey conducted with parents are also returned. In total, the research shows a relationship with the school made of mistrust and expectations often disappointed. Coeducation, the objective of which is to encourage the involvement of parents in the educational institution, applies to the schooling of children of “itinerant families and travelers” in a singular mode where institutional control seems to respond to mistrust parental. The attempt to educate parents to respect school attendance and to meet school requirements appears to be thwarted by parental expectations that are out of step with the French school’s individual emancipation project.